Numerical Simulations of Particle Sedimentation Using the Immersed Boundary Method (Communications in Computational Physics, 2018)
We study the settling of solid particles in a viscous incompressible fluid containedwithin a two-dimensional channel, where the mass density of the particles isgreater than that of the fluid. The fluid-structure interaction problem is simulatednumerically using the immersed boundary method, where the added mass is incorporatedusing a Boussinesq approximation. Simulations are performed with a singlecircular particle, and also with two particles in various initial configurations. The terminalparticle settling velocity and drag coefficient correspond closely with other theoretical,experimental and numerical results, and the particle trajectories reproducethe expected behavior qualitatively. In particular, simulations of a pair of interactingparticles similar drafting-kissing-tumbling dynamics to that observed in other experimentaland numerical studies.